The Effect of Focus Group Discussion Learning Method on Cognitive Ability and Cooperation Skills of Students on Redox Material - Vivin Fasihatul Harfiah; Setia Rahmawan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This research was motivated by the misconceptions about teacher learning methods in chemistry subjects. This study aims to determine the effect of Focus Group Discussion method on cognitive abilities and cooperation skills of students on redox material. The research method used is quasi experiment. The results showed that the application of learning with the Focus group discussion method was more effective than the lecture method. Based on the statistical analysis test of the cognitive ability of the experimental class, the average value of the pretest and posttest was 62.79 and 74.85, respectively. In the control class, the average pretest and posttest scores were 61.76 and 69.41, respectively. The results of the cooperation skills analysis test of the experimental class obtained an average value of 63, 35, and 75, 76. In the control class, the average pretest and posttest scores were 29.65 and 38.47, respectively. Overall, the data showed that the application of the Focus Group Discussion learning method was able to improve the cognitive abilities and cooperation skills of students in understanding abstract concepts in redox material. Thus, the Focus Group Discussion method is potential to be applied in other STEM learning materials to encourage active attitudes and critical thinking of students in learning.